Why Trade When You Can Transfer the Technology: Revisiting Smith and Ricardo - Rajat Acharyya; Sugata Marjit (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper explores the possibility of international technology transfer in lieu of trade in a model with absolute and comparative advantage. Countries having absolute advantage in producing a good may offer that technology to a possible trading partner against a fee and both the countries might gain. Thus, gains from trade might be dominated by gains from technology transfer depending on the extent of comparative and absolute advantages. We provide detailed conditions under which free trade equilibrium will be pre-empted by technology transfer. Such an avenue of fruitful exchange remains unexplored in the Ricardian model of trade.
Keywords: F10; 330; technology transfer; absolute advantage; comparative advantage; Smith; Ricardo